2002
DOI: 10.1093/geronb/57.6.s366
|View full text |Cite
|
Sign up to set email alerts
|

Use, Type, and Efficacy of Assistance for Disability

Abstract: The results about equipment give impetus to policies that promote development and dissemination of assistive technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 32 publications
7
59
1
4
Order By: Relevance
“…In addition, although both aids and personal assistance reduce task demand, they do not accomplish this in the same manner (3), nor are they used under the same circumstances. Autonomy and self-sufficiency are maintained when equipment is used, but are lost with assistance (3,18). Personal assistance may be dependent upon resources available, such as living with a spouse (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although both aids and personal assistance reduce task demand, they do not accomplish this in the same manner (3), nor are they used under the same circumstances. Autonomy and self-sufficiency are maintained when equipment is used, but are lost with assistance (3,18). Personal assistance may be dependent upon resources available, such as living with a spouse (18).…”
Section: Discussionmentioning
confidence: 99%
“…In their study of elderly community residents, Verbrugge and Sevak (2002) found severity of disability and need were strongly associated with assistance use. Also, among the severely disabled, equipment assistance was preferred over personal assistance.…”
Section: Measurement Of Disability and Disability Life Expectancy Milmentioning
confidence: 97%
“…Disability, in this framework, is a gap between personal capability and environmental demand (Verbrugge and Jette, 1994). The social and physical environment may become more hospitable for the disabled through the use of personal and equipment assistance, both of which serve as buffers that reduce dysfunction (Verbrugge and Sevak, 2002).…”
Section: Measurement Of Disability and Disability Life Expectancy Milmentioning
confidence: 99%
“…In the future, however, as people have fewer children, it is expected that more people will be dependent on assistive devices for basic mobility (47). Importantly, delay or lack of access to this equipment may cause negative and more costly health conditions (48).…”
Section: Assistive Devicesmentioning
confidence: 99%